Letter from Adrian Stokes to Herbert Read, March 03, 1939 - http://id.worldcat.org/fast/1733311 (1939)
Part of a collection of correspondence between Adrian Stokes and Herbert Read spanning from 1934-1962. Stokes was a painter and art critic who also had an interest in psychoanalysis. It was largely due to his efforts and work that the small fishing port of St. Ives became a centre of modernist art culture.